2020
DOI: 10.3390/ijms21218004
|View full text |Cite
|
Sign up to set email alerts
|

MRI Radiomic Features to Predict IDH1 Mutation Status in Gliomas: A Machine Learning Approach using Gradient Tree Boosting

Abstract: Patients with gliomas, isocitrate dehydrogenase 1 (IDH1) mutation status have been studied as a prognostic indicator. Recent advances in machine learning (ML) have demonstrated promise in utilizing radiomic features to study disease processes in the brain. We investigate whether ML analysis of multiparametric radiomic features from preoperative Magnetic Resonance Imaging (MRI) can predict IDH1 mutation status in patients with glioma. This retrospective study included patients with glioma with known IDH1 status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…IDH1 Arg132His (R132H) mutation can affect the proliferation of glioma cells, which is slower than the corresponding wild-type IDH1 cells ( 8 , 9 ). Clinical studies ( 10 , 11 ) have shown that mutations in IDH1 were found to be associated with younger age, secondary GBMs (grade IV tumors that arise from biopsy-proven lower-grade predecessors), and increased overall survival (OS) ( 12 ). Further studies ( 13 , 14 ) have revealed that IDH1/2 mutations as good prognostic markers are universally present in grade II and III glioma and secondary glioblastoma, and serve an important role in the occurrence, development and evolution of glioma ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…IDH1 Arg132His (R132H) mutation can affect the proliferation of glioma cells, which is slower than the corresponding wild-type IDH1 cells ( 8 , 9 ). Clinical studies ( 10 , 11 ) have shown that mutations in IDH1 were found to be associated with younger age, secondary GBMs (grade IV tumors that arise from biopsy-proven lower-grade predecessors), and increased overall survival (OS) ( 12 ). Further studies ( 13 , 14 ) have revealed that IDH1/2 mutations as good prognostic markers are universally present in grade II and III glioma and secondary glioblastoma, and serve an important role in the occurrence, development and evolution of glioma ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the other four algorithms (support vector machine, random forest, naive Bayes, and logistic regression algorithms), this model showed the highest accuracy in ovarian cancer diagnosis [29]. As for gliomas, it improved the classi cation of MGMT promoter methylation status in IDH1 wildtype GBM [30], e ciently classi ed transcriptome subtypes in GBM patients from MRI [31], and predicted IDH1 mutation status in gliomas [32]. In our study, this method classi ed different VEGF expression statuses in GBM with good results.…”
Section: Discussionmentioning
confidence: 98%
“…The XGBoost algorithm is based on gradient boosting decisionmaking, has low data requirements, fast training speed, and accurate training results. It has been widely used in artificial intelligence and the data analysis fields, and has been increasingly used in clinical research (9,10). This study retrospectively analyzed patients who received surgical treatment for glioma for the first time.…”
Section: Introductionmentioning
confidence: 99%